Patentanmeldungen im Ruhrgebiet — Stärken und Schwächen im Vergleich von Agglomerationen - Kampmann, Ricarda (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
Patent applications — a result of innovation activities and a leading indicator for technical developments — are concentrated in agglomerations. Therefore, patent applications from the Ruhr Area are compared with those in other urban centres. Their level and development within the Ruhr area are below average. Nevertheless, they possess certain strengths: in some technical fields such as chemistry an above-average proportion and development can be observed. In addition, there is a bigger variability of patent applications within the Ruhr area than in other regions. Additionally, there are other nearby areas with a high level of researching activities in NRW. Consequently, networking seems to be more promising than in other federal states in Germany.